Context of the Text of the Production of the Policy of International Academic Cooperation Agreements of a Federal University (Research, Society and Development, 2021)
This research aimed to analyze policy documents that support the International Academic Cooperation Agreements of a federal university, in order to verify their importance for the academic and regional/local community. It is a documentary research that uses the context of the policy text production of Stephen J. Ball's Policy Cycle. For this purpose, data collection was carried out through the analysis of three institutional documents: General Regulations, Institutional Plan for Internationalization and the Institutional Development Plan (2019-2023), with approaches in Discursive Textual Analysis. It was concluded that the University recognizes the importance of internationalization as a way to improve the quality of teaching, but there is still a lack of institutional alignment to formalize the actions of Cooperation Agreements. The university is also perceived as a means of mobilizing actions and knowledge production in different social spaces. It enabled the expansion of knowledge about internationalization and fostered reflections on educational innovation as an instrument that should be included in the International Academic Cooperation Agreements. For this, expand and strengthen inter-institutional relations, especially in the neighboring country, boosting regional and local development.